Episode 1: Introducing...Policy Pathways - International Water Management Institute (CGIAR Initiative on National Policies and Strategies, 2024)
Confronting sustainable development challenges requires system transformation in Food, Land, and Water! Policy Pathways invites policymakers and sustainable development stakeholders to share their expertise on the policy solutions that can advance system transformation across the globe. CGIAR Research Initiative on National Policies and Strategies has produced a series of policy coherence reports focused on India, Colombia, Nigeria, Kenya, Egypt, and Laos. Each of these reports looks in detail at country-specific challenges and makes recommendations for the incorporation of policy tools that can lead to a sustainable future. Come with us as our hosts Chhavi Sachdev and Raissa Okoi explore the international potential of policy coherence with the people doing the vital work. Policy Pathways is brought to you by CGIAR's National Policies and Strategies Initiative and is produced by the International Water Management Institute (IWMI).